Pengembangan Kurikulum Pesantren Pelajar - Wafi Ali Hajjaj (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam Syarifuddin Lumajang, 2017)
One of the efforts that must be taken to anticipate the global changes and the demands of the progress of science and technology, and to increase and equalize the quality of the graduates is through curriculum development efforts. In the world of education, the curriculum becomes one of the decisive factors for the success of graduates in entering the workforce. The curriculum is the core / heart of eeducation, the curriculum is the core or the heart of education. It is said that because the curriculum me elaboration of idealism, ideals, community demands, or certain needs. The direction of education, educational alternatives, educational functions and educational outcomes are highly dependent and dependent on the curriculum. Pesantren education which is presented with boarding school system or dormitory is the right step as preventive action for students to influence environment that is not appropriate because of moral of nation which is getting far from humanity and religion teachings, students have experienced mental crisis and morals, they are stuck at drugs, promiscuity, fights between students, brave of parents.